Development of Synchronous Transportation Model for Trackless Vehicle Dispatching During the Construction of Long-Distance Single-Headed Shield Tunnel - Jian Wu; Shao-Hui Tang; Chui-Yi Zhou; Yong Huang; Lei Huang; Hong-Bo Lu; Ning Miao (Advances in Civil Engineering)
With the increasing demands for long-distance single-headed tunnels, trackless vehicles have been widely accepted for transporting construction materials from storage yard to working face. During the trackless transportation of construction materials, the synchronization of material supply and shield tunneling is critical to ensure tunneling efficiency. However, there is still a lack of a reliable synchronous transportation model for trackless vehicle dispatching. In the present study, the material transportation processes and vehicle transportation parameters have been investigated based on the Sutong GIL Yangtze River Crossing Cable Tunnel. The synchronous transportation model has been established to improve transportation efficiency during the construction stage. An optimized scheme of vehicle schedule has been proposed to minimize trackless vehicle and retention time. Comparative analysis has been carried out to evaluate the trackless vehicle and retention time between the optimized scheme and the original scheme. The results indicate that the number of dual-headed trucks required for material transportation decreases from nine to six, and the maximum retention time decreases from 166 to 35 min. Compared with the original scheme, the optimized scheme is available for reducing the number of trackless vehicles and improving the efficiency of material transportation. The present study contributes to optimizing material transport scheduling and synchronizing material supply with tunnel excavation in long-distance single-headed shield tunnels.